Corporate Financial Reporting: The Issues, the Objectives and Some New Proposals. - Zlatkovich, Charles T.; Spiller, Earl A. (The Accounting Review, 1973)
Abstract The article reviews the book "Corporate Financial Reporting: The Issues, the Objectives and Some New Proposals," edited by Alfred Rappaport and Lawrence Revsine.